PERAN PERTANIAN KELUARGA (FAMILY FARMING) DI MASA PANDEMI COVID-19 - Ivan Sayid Nurahman; Rian Kurnia; Saepul Aziz (Universitas Galuh, 2022)
FAO as an international institution that focuses on food and agriculture issues in the world has ordered since the end of 2019 regarding the potential for the global food crisis that occurs in the Covid-19 pandemic. This is a major concern for Indonesia, which has been relying on imports to meet food needs. Again with distribution problems caused by the PSBB policy, because food is added to the basic needs that must be met by every community. Family farming is an alternative to survive (food security) in the midst of a pandemic. In the global context, family farming has now been seen as an approach to food security from food security, improved nutrition as well as increased family welfare. This study aims to see the role of family farming applications in family food security in Binangun Village, Pataruman, Banjar City. Responses were chosen purposively as many as 33 female farmers who are members of the Puncaksari Women Farmers Group. The data used include primary and secondary data during 2020 using in-depth interview techniques, focused discussions and literature studies. The data collected was collected descriptively using the interactive model of Miles and Huberman. The results showed that family farming was able to play a role as a positive and productive activity during the pandemic, providing family food, increasing income, avoiding erratic food commodity price fluctuations, and maintaining the health of the environment and family.